REMAKES TRANSNACIONALES: DINÁMICAS INDUSTRIALES Y ESTÉTICAS - FERNÁNDEZ LABAYEN, Dr. MIGUEL,MARTÍN MORÁN, Dra. ANA (Fonseca, Journal of Communication, 2023)
This article studies the industrial and aesthetic dynamics of transnational film remakes, focusing on both the production and circulation strategies as well as the narrative adaptation tactics involved in any remake process. In order to do so, we examine the films ¿Quién mató a Bambi? (Santi Amodeo, 2013), a remake of the Mexican film Matando Cabos(Alejandro Lozano, 2004) and Kiki, love to love (Paco León, 2016), a version of the Australian The Little Death (Josh Lawson, 2014).